2007
DOI: 10.1098/rsta.2007.2077
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for probabilistic predictions of regional climate change from perturbed physics ensembles

Abstract: A methodology is described for probabilistic predictions of future climate. This is based on a set of ensemble simulations of equilibrium and time-dependent changes, carried out by perturbing poorly constrained parameters controlling key physical and biogeochemical processes in the HadCM3 coupled ocean-atmosphere global climate model. These (ongoing) experiments allow quantification of the effects of earth system modelling uncertainties and internal climate variability on feedbacks likely to exert a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
258
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(259 citation statements)
references
References 124 publications
(233 reference statements)
1
258
0
Order By: Relevance
“…UKCP09 are probabilistic projections developed by the UK Met Office to provide climate change projections of climate change over the UK with greater spatial and temporal detail than previous climate scenarios. They are based on the results of the HadCM3 coupled ocean-atmosphere Global Circulation Model (Gordon et al, 2000), run as a perturbed physics ensemble to sample model and parameter uncertainties (Murphy et al, 2007). HadCM3 projections were then downscaled on a 25 km grid over seven overlapping 30-yr time periods based on an ensemble of 11 variants of the regional climate model HadRM3, and a statistical procedure was applied to build local-scale distributions of changes for various climate variables.…”
Section: Risk Of Change In Phytoplankton Concentrationmentioning
confidence: 99%
“…UKCP09 are probabilistic projections developed by the UK Met Office to provide climate change projections of climate change over the UK with greater spatial and temporal detail than previous climate scenarios. They are based on the results of the HadCM3 coupled ocean-atmosphere Global Circulation Model (Gordon et al, 2000), run as a perturbed physics ensemble to sample model and parameter uncertainties (Murphy et al, 2007). HadCM3 projections were then downscaled on a 25 km grid over seven overlapping 30-yr time periods based on an ensemble of 11 variants of the regional climate model HadRM3, and a statistical procedure was applied to build local-scale distributions of changes for various climate variables.…”
Section: Risk Of Change In Phytoplankton Concentrationmentioning
confidence: 99%
“…Although GCMs can reproduce important salient features of the current climate, projections of future climate produced by different climate models can vary substantially at the regional scale [Cubasch et al, 2001]. The latter may result because some physical assumptions suitable for the current situations may break down as the climate evolves or because compensating errors that exist among the parameterization schemes for different physical processes no longer cancel out in the future [Gilmore et al, 2004;Molders, 2005;Golaz et al, 2007;Min et al, 2007;Murphy et al, 2007]. Ensemble simulations with multiple models or parameterizations have been applied as effective approaches to characterize uncertainties associated with dynamical or physical processes in the model [Allen et al, 2000;Giorgi and Mearns, 2002;Stainforth et al, 2005;Lopez et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Both these strategies have potential advantages but also many challenges, as discussed by Hall et al (2014). The two fundamental problems connected with climate impact assessments can be summarized as follows: (1) observed time series can include natural long-term cycles that might be induced by climatic oscillations or persistent memory of hydrological processes (Markonis and Koutsoyiannis, 2012;Montanari, 2012), which will render all statistical trend analyses very sensitive to the period chosen for the study; and (2) global climate models (GCMs) do not correspond to the observed climatology (Murphy et al, 2007), and uncertainties arise in each step of the model chain in hydrological impact assessments Donnelly et al 2014). Much effort has been made over the last decade to address these prob-i.…”
Section: Introductionmentioning
confidence: 99%